Jejunojejunal Intussusception Induced by a Gastrointestinal Stromal Tumor. (19th November 2012) - Zakaria, Ali H.; Daradkeh, Salam
Abstract : Background . Adult intussusception is a rare entity representing less than 1% of all intestinal obstructions. Diagnosis of the condition is difficult requiring a high index of suspicion and the utilization of imaging studies, especially CT scans. Diagnostic laparoscopy and/or exploratory laparotomy can be used as a diagnostic and therapeutic intervention. In over 90% of cases, an underlying lead point is identified. In the patient described here, it was a gastrointestinal stromal tumor (GIST), a relatively rare mesenchymal tumor comprising only 0.2–1.0% of the gastrointestinal tract neoplasms and believed to originate from neoplastic transformation of the interstitial cells of Cajal. GISTs may occur anywhere along the gastrointestinal tract, but most commonly arise in the stomach and small intestine. Literature review revealed only few cases reporting GISTs as a leading point of adult's intussusception. Case Presentation . In this report, we are presenting a rare case of jejunojejunal intussusception in a 78-year-old female patient with a GIST located in the terminal jejunum being the leading point, demonstrating the importance of imaging studies, especially CT scan, laparoscopy, and exploratory laparotomy as diagnostic and therapeutic interventions.